The Effect of Problem-Based Learning Model Accompanied by the QuizWhizzer Game on Critical Thinking Skills and Physics Learning Outcomes of Vocational Students - Zhahrotun Nurroniah; Subiki Subiki; Lailatul Nuraini (Berkala Ilmiah Pendidikan Fisika, 2024)
Physics learning is learning that influences students' thinking skills so that students can be skilled in the cognitive and psychomotor fields and support students to think systematically, creatively, and objectively. But in fact, the implementation of learning that occurs is not contextual because the way teachers teach in class is still boring and less varied, so student involvement in the learning process in class becomes less active, both asking and answering questions. This study aims to determine the effect of using a problem-based learning model accompanied by a QuizWhizzer game on vocational students' critical thinking skills and physics learning outcomes in Jember Regency. This study used a quantitative approach, specifically a true experimental design of a posttest-only control group. The study population consisted of class X students at SMK Negeri 1 Jember, with the sample comprising two classes selected from all classes at SMK Negeri 1 Jember. Data analysis of students' critical thinking skills using the Mann-Whitney U Test resulted in a significance value (2-tailed) of 0.038 < 0.05, which leads to the rejection of H0 and acceptance of Ha. Data analysis of students' physics learning outcomes using the Mann-Whitney U Test and hypothesis testing results resulted in a significance value (2-tailed) of 0.023 < 0.05, which leads to the rejection of H0 and acceptance of Ha. These findings indicate a significant effect of applying a problem-based learning model assisted by QuizWhizzer on students' critical thinking skills and physics learning outcomes, especially on energy and its changes. With this research, teachers can design more effective learning models to support critical thinking skills and optimal student learning outcomes in physics learning accompanied by learning media by analysing student needs, selecting learning models, developing learning media, planning learning activities, and implementing them.